The Training Needs and the Expectation of Career Planning of Dusit Thani College’s Education Officer - Nalinee Phansaita นลินี พานสายตา; Praweena Kasai ประวีณา คาไซ (Dusit Thani College Journal, 2018)
The study of the training needs and the expectation of career planning of Dusit Thani College’s education officer was a survey research. This research aimed to study the training needs of Dusit Thani College’s education officer, the expectation of career planning of education officer and the relationship between the training needs and the expectation of career planning of education officer. A sample group was education officer of private higher education institution. The total number of respondents to the survey was 69 by applying stratified random sampling. A questionnaire was the tool used for collecting data. Descriptive statistics and Pearson product moment correlation coefficient were applied. The result found that the training needs level of Dusit Thani College’s education officer in term of training and training styles is high while the training needs level in terms of education is moderate. However, the level of career planning expectation in terms of position/duty/ responsibility is moderate and the level of career planning in terms of compensation is high. The research also found that there is a significant relationship between training needs in terms of training, education and training styles of Dusit Thani College’s education officer to the expectation of career planning in terms of position/duty/responsibility. However, there is a significant relationship between training needs only in terms of training (technical training) and training styles of Dusit Thani College’s education officer to the expectation of career planning in term of compensation. The research found no relationship between training needs in terms of training (Managerial training and Interpersonal training) and education to the career planning in terms of compensation.